Functional analysis of the heterotrimeric NF-Y transcription factor complex in cassava disease resistance. (6th July 2019) - He, Xinyi; Liu, Guoyin; Li, Bing; Xie, Yanwei; Wei, Yunxie; Shang, Sang; Tian, Libo; Shi, Haitao
Abstract: Background and Aims: The nuclear factor Y (NF-Y) transcription factor complex is important in plant growth, development and stress response. Information regarding this transcription factor complex is limited in cassava ( Manihot esculenta ). In this study, 15 MeNF-YA s, 21 MeNF-YB s and 15 MeNF-YC s were comprehensively characterized during plant defence. Methods: Gene expression in MeNF-Ys was examined during interaction with the bacterial pathogen Xanthomonas axonopodis pv. manihotis ( Xam ). The yeast two-hybrid system was employed to investigate protein–protein interactions in the heterotrimeric NF-Y transcription factor complex. The in vivo roles of MeNF-Y s were revealed by virus-induced gene silencing (VIGS) in cassava. Key Results: The regulation of MeNF-Y s in response to Xam indicated their possible roles in response to cassava bacterial blight. Protein–protein interaction assays identified the heterotrimeric NF-Y transcription factor complex (MeNF-YA1/3, MeNF-YB11/16 and MeNF-YC11/12). Moreover, the members of the heterotrimeric NF-Y transcription factor complex were located in the cell nucleus and conferred transcriptional activation activity to the CCAAT motif. Notably, the heterotrimeric NF-Y transcription factor complex positively regulated plant disease resistance to Xam, confirmed by a disease phenotype in overexpressing plants in Nicotiana benthamiana and VIGS in cassava. Consistently, the heterotrimeric NF-Y transcription factor complex positively regulated the expression of pathogenesis-related genes ( MePR s). Conclusions: The NF-Y transcription factor complex (MeNF-YA1/3, MeNF-YB11/16 and MeNF-YC11/12) characterized here was shown to play a role in transcriptional activation of MePR promoters, contributing to the plant defence response in cassava.